Clinical and psychological course of diabetes from adolescence to young adulthood: a longitudinal cohort study. - Bryden, K; Peveler, R; Stein, A; Neil, A; Mayou, R; Dunger, D (2001)
OBJECTIVE: To determine the clinical and psychological course of diabetes through adolescence and the relationship with glycemic control in young adulthood. RESEARCH DESIGN AND METHODS: A longitudinal cohort study of adolescents recruited from the register of the outpatient pediatric diabetes clinic. A total of 76 individuals (43 male patients, 33 female patients) aged 11-18 years completed baseline assessments, and 65 individuals (86%) were reinterviewed as young adults (20-28 years of age). Longitudinal assessments were made of glycemic control (HbA(1c)), weight gain (BMI), and development of complications. Adolescents completed self-report questionnaires to assess emotional and behavioral problems as well as self-esteem. As young adults, psychological state was assessed by the Revised Clinical Interview Schedule and the self-report Brief Symptom Inventory. RESULTS: Mean HbA(1c) levels peaked in late adolescence and were worse in female participants (average 11.1% at 18-19 years of age). The proportion of individuals who were overweight (BMI >25.0 kg/m(2)) increased during the 8-year period from 21 to 54% in female patients and from 2 to 28% in male patients. Serious diabetes-related events included death in one patient and cognitive impairment in two patients. Individuals in whom diabetic complications developed (25% of male patients and 38% of female patients) had significantly higher mean HbA(1c) levels than those without complications (difference 1.9%, 95% CI 1.1-2.7, P < 0.0001). Behavioral problems at baseline were related to higher mean HbA(1c) during the subsequent 8 years (beta = 0.15, SEM (beta) 0.04, P < 0.001, 95% CI 0.07-0.24). CONCLUSIONS: The outcome for this cohort was generally poor. Behavioral problems in adolescence seem to be important in influencing later glycemic control.